CORRIGENDUM TO "PROTOTYPE OF WEB-BASED DAILY WORK REPORT MANAGEMENT SYSTEM USING SMART PENS" - Chen, Tim; Muḥammad, Abū al-Qāsim; Chen, John; Hassan Sajib, Himel Md Sakibul (Journal of Applied Engineering Science, 2021)
Prof. Dr. Gradimir Danon, Editor in Chief of the Journal of Applied Engineering Science demanded the change in the list of the contributing authors.CLARIFICATIONUpon written remarks of Dr. Alexander Babanin from University of Melbourne, Melbourne, Australia and Dr. Bertrand Chapron from Laboratoire d'Océanographie Physique et Spatiale, Centre de Brest, IFREMER, Plouzané, France that each of them was included in the list of co-authors without their acceptance and knowledge, and written apology of the corresponding author Dr. John Chen explaining it was his omission, the Editorial Board decided to correct the list of initially listed authors.Therefore, initial authors list from the above stated paper published under the paper number 17(2019)3, 607, 280-283 with DOI:10.5937/jeas10-18602:Tim Chen1, Alexander Babanin2, Abū al-Qāsim Muḥammad3, Bertrand Chapron4, John Chen5,6*,Himel Md Sakibul Hassan Sajib6,71Al LAB, Faculty of Information Technology, Ton Duc Thang University, Ho Chi Minh City, Vietnam2University of Melbourne, Melbourne, Australia3King Abdulaziz University, Jeddah, Saudi Arabia4Laboratoire d'Océanographie Physique et Spatiale, Centre de Brest, IFREMER, Plouzané, France5Staffordshire University, Staffordshire, United Kingdom6BRAC University, Dhaka, Bangladesh7Asia Pacifi c University, Kuala Lumpur, Malaysiahas to be written as follows:Tim Chen1, Abū al-Qāsim Muḥammad2, John Chen3,4*, Himel Md Sakibul Hassan Sajib4,51Al LAB, Faculty of Information Technology, Ton Duc Thang University, Ho Chi Minh City, Vietnam2King Abdulaziz University, Jeddah, Saudi Arabia3Staffordshire University, Staffordshire, United Kingdom4BRAC University, Dhaka, Bangladesh5Asia Pacific University Kuala Lumpur, MalaysiaExclusion of Dr. Alexander Babanin and Dr. Bertrand Chapron does not affect original paper.